IMPROVING THE STUDENTS’ VOCABULARY THROUGH MONOPOLY GAMES AT THE EIGHTH GRADE STUDENTS OF MADRASAH TSANAWIYAH SWASTA MADINATUSSALAM SEI ROTAN PERCUT SEI TUAN - MATONDANG, MELATI (BRIGHT VISION Journal of Language and Education, 2021)
This research aims to improvement of students’ vocabulary by using monopoly games. This research was conducted to determine the improvement of students’ vocabulary by using monopoly games. The number of students consists of 30 students who are used by the researcher as respondents.   The research of this study was conducted by using classroom action research. Quantitative data and qualitative data were used as data analysis technique in this study. The results of the  qualitative  data  were  taken  through  the  results  of  observation  sheet, interviews, and documentation while the quantitative data were taken through the result of students test. In this research, the researcher collected data with two cycles. Where, there were 5 students got successfull score criteria or it was only 16,66 % and 25 students’ got unsuccessful or it was 83,34%. After doing cycle I by using monopoly games, there was an improving of the result of the students’ mean was 57.87.  Criteria or score it was 90 % and 3 students’ got unsuccessful criteria score or it was 10%. In other words, the data above shows that   the students’ vocabulary mastery was increased. And based on interviewed, observation sheet, and photographs, it showed that the expression and enthusiasm in learning of the students were also improve. Keywords : Vocabulary  and Monopoly games